Formulation and Evaluation Study of Polyherbal Formulations towards Antidiabetic, Antilipidemic and Water Intake - Aher , Sunil J.; Patil , Poonam; Dashpute , Ashish Vinod; Mahajan , Kiran C.; Wakale , Vijaykumar S.; Joshi , Supriya C. (International Journal of Membrane Science and Technology, 2023)
Present investigation has to undertake for estimation of Antidiabetic, antilipidemic and water intake study in Polyherbal formulation. Total flavonoid content was64.01 mg/ml which is catechin equivalent, while Total phenolic content was 142.20 mg/ml, it shown strong anti-oxidant properties are indicated by the relatively high gallic acid content. The polyherbal juice’s DPPHactivity was found to be 68.45% and for polyherbal formulations A and B to be 55.04% and 58.85%. The RC50 value for the DPPH scavenging assay was reported to be 6.0 g/ml. Quantitative Analysis of Phytoconstituents in Formulation was carried out using preliminary phytochemical assays and HPTLC.